Caregivers and Alzheimer’s Disease Through the Covid-19 Pandemic - Altable, Marcos; De la Serna Tuya, Juan Moisés (Journal of Drug and Alcohol Research, 2023)
COVID-19 pandemic has carried a high number of deaths worldwide. Most of those who died were older adults, especially who previously suffered from health problems. This population are more vulnerable, especially during the expansion and subsequent pandemic by COVID-19. Since higher levels of distress, anxiety and depression were observed among caregivers of dementia patients and Alzheimer’s disease individuals, we may be able to prevent or reduce the harm of the COVID-19 pandemic and its consequences for patients with AD and related dementias (ADRD) and their caregivers.
Keywords: Alzheimer’s; COVID-19; Dementia; Scopus